1998
DOI: 10.1289/ehp.98106s1231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glutathione S-transferase M1 polymorphisms on biomarkers of exposure and effects

Abstract: Genotypes responsible for interindividual differences in ability to activate or detoxify genotoxic agents are recognized as biomarkers of susceptibility. Among the most studied genotypes are human glutathione transferases. The relationship of genetic susceptibility to biomarkers of exposure and effects was studied especially in relation to the genetic polymorphism of glutathione S-transferase M1 (GSTM1). For this review papers reporting the effect of GSTM1 genotype on DNA adducts, protein adducts, urine mutage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 41 publications
0
18
0
1
Order By: Relevance
“…However, there is no consistent evidence supporting this association. Some studies have found a higher level of DNA adducts and chromosome damage in lymphocytes of coke oven workers, bus drivers and tobacco smokers who lack the GSTM1 gene, 24,[105][106][107][108] whereas others failed to find a significant relationship. 109,110 The same can be said for CYP1A1 polymorphisms.…”
Section: Controlsmentioning
confidence: 99%
“…However, there is no consistent evidence supporting this association. Some studies have found a higher level of DNA adducts and chromosome damage in lymphocytes of coke oven workers, bus drivers and tobacco smokers who lack the GSTM1 gene, 24,[105][106][107][108] whereas others failed to find a significant relationship. 109,110 The same can be said for CYP1A1 polymorphisms.…”
Section: Controlsmentioning
confidence: 99%
“…The age range of the patients with gastric cancer was 30-84 years (mean age, 62.5 Ϯ 11.3 years; there were 98 men and 49 women). The control study with age-matched autopsy subjects (age at death, 20-95 years; mean age, 64.0 Ϯ 17.5 years; 74 men and 38 women) excluded patients with stomach, lung, urinary bladder, or colon cancer, because several studies have indicated that GSTM1 deficiency is a risk factor for the development of these cancers [1,3,5]. Smoking histories were not available in this study, because the information was incomplete in a considerable number of the cases and controls.…”
Section: Study Subjects and Dna Preparationmentioning
confidence: 99%
“…Glutathione S-transferase M1 (GSTM1), a member of the GST mu family, is one of the most studied genotypes in relation to the individual susceptibility to cancers. For example, a considerable number of investigations indicate that individuals with a homozygous deletion of the GSTM1 gene (GSTM1 null genotype) are susceptible to lung and urinary bladder cancers [1,3,5]. However, the link between the GSTM1 polymorphism and gastric carcinoma is controversial [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Glutathione S-transferases (GSTs) are phase II enzymes and responsible for catalyzing the biotransformation of a variety of electrophiles, and have a central role in the detoxification of activated metabolites of procarcinogens produced by phase I reactions. GSTM1 conjugates xenobiotics with glutathione [4] which promotes the removal of activated carcinogens from the human body. Esophageal cancer (EC) is one of the most common malignant diseases worldwide with a sharp variation in its geographic distribution [5] .…”
Section: Introductionmentioning
confidence: 99%